Nonlinear Dynamics, Volume 1 Proceedings of the 33rd IMAC, A Conference and Exposition on Structural Dynamics, 2015 - Kerschen, Gaëtan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Nonlinear Dynamics, Volume 1.  Proceedings of the 33rd IMAC, A Conference and Exposition on Balancing Simulation and Testing, 2015, the first volume of ten from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Nonlinear Oscillations Nonlinear Simulation Using Harmonic Balance Nonlinear Modal Analysis Nonlinear System Identification Nonlinear Modeling & Simulation Nonlinearity in Practice Nonlinear Systems Round Robin on Nonlinear System Identification.
Interplay between local frictional contact dynamics and global dynamics of a mechanical system -- Non linear dynamics of jointed systems under dry friction forces -- Prediction of nonlinear forced response on ancillary subsystem components attached to reduced linear systems -- Numerical round robin for prediction of dissipation in lap joints -- The harmonic balance method for bifurcation analysis of nonlinear mechanical systems -- Nonlinear vibrations of a beam with a breathing edge crack -- Stability limitations in simulation of dynamical systems with multiple time-scales -- Coupled parametrically driven modes in synchrotron dynamics -- Relating backbone curves to the forced responses of nonlinear systems -- Nonlinear modal interaction analysis for a three degree of freedom system with cubic nonlinearities -- Passive flutter suppression using a nonlinear tuned vibration absorber -- Nonlinear vibrations of a flexible l-shaped beam using differential quadrature method -- Theoretical and experimental analysis of bifurcation induced passive bandgap reconfiguration -- A model of evolutionary dynamics with quasiperiodic forcing -- Experimental demonstration of a 3d printed nonlinear tuned vibration absorber -- The effect of gravity on a slender loop structure -- Wave propagation in a materially nonlinear rod -- Experimental nonlinear dynamics and chaos of post buckled plates -- Control based continuation of a hybrid numerical/physical substructured system -- Towards finite element model updating based on nonlinear normal modes -- Experimental modal analysis of nonlinear structures using broadband data -- Measurement of nonlinear normal modes using mono harmonic force appropriation -- Nonlinear system identification through backbone curves and bayesian inference -- Experimental nonlinear identification of an aircraft with bolted connections -- Non linear finite element model validation of a lap-joint -- Experimental validation of pseudo receptance difference (prd) method for nonlinear model updating -- Systems with bilinear stiffness -- Simplifying transformations for nonlinear systems: part i, an optimisation-based variant of normal form analysis -- Simplifying transformations for nonlinear systems: part ii, statistical analysis of harmonic cancellation -- considerations for indirect parameter estimation in nonlinear reduced order models -- Nonlinear model updating methodology with application to the imac xxxiii round robin benchmark problem -- Bridging the gap between nonlinear normal modes and modal derivatives -- Validation of nonlinear reduced order models with time integration targeted at nonlinear normal modes -- Model order reduction of nonlinear Euler Bernoulli beam -- Identification of dynamic nonlinearities of bolted structures using strain analysis -- The effects of boundary conditions measurement techniques and excitation type on measurements of the properties of mechanical joints -- Numerical model for elastic contact simulation -- Efficient and accurate consideration of nonlinear joint contact within multibody simulation -- Model reduction for nonlinear multibody systems based on proper orthogonal  & smooth orthogonal decomposition -- Cam geometry generation and optimization for torsion bar systems -- Dynamics modelling and accuracy evaluation of a 6-dof hexaslide robot -- A belt-driven 6-dof parallel kinematic machine -- Bearing cage dynamic cage failure and bearing life estimation -- Bias errors of different simulation methods for linear and nonlinear systems -- Internal resonance and stall flutter interactions in a pitch flap wing in the wind-tunnel.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Nonlinear Optics; Solids; Multibody Systems and Mechanical Vibrations; Nonlinear Optics; Solid Mechanics